The Meanings of Symbols of Priyambada Mustakaweni Dance - merdekawati, Ika; Malarsih, Malarsih; Sunarto, Sunarto (Universitas Negeri Semarang, 2019)
This Research Aimed At Expressing The Meaning Of Symbols Of Priyambada Mustakaweni Dance. It Is Used Qualitative Method. The Data Collecting Techniques Were Through Observation, In Depth Interview, And Documentation. The Data Validation Used Data Triangulation Technique And Informan Review. The Data Was Analyzed Through The Process Of Reduction, Presentation, And Data Verification. The Results Of The Research Are That The Performance Form Of Priyambada Mustakaweni Dance Consist Of Title, Theme, Number Of Dancers, Movements, Place, Accompaniment, Makeup And Costume, Property, And Lighting. The Meaning Of Priyambada Mustakaweni Dance Is Reflected Through The Movements Perang Tantang-Tantangan, Perang Keris And Perang Gendhewa. (1) Perang Tantang-Tantangan Has A Meaning Of A Brave Female Soldier And Ready To Fight For The Country, (2) Perang Keris, Has An Implied Meaning That A Soldier Ha A Strategy And Power To Defend His Country, (3)Perang Gendhewa Implies That A Soldier Should Be Trained And Is Always Alert From Enemy’s Attack. Kata kunci : Tari Priyambada Mustakaweni, Bentuk, Makna Simbol.